2010
DOI: 10.1097/sla.0b013e3181b2f6ee
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Lymphadenectomy for Esophageal Cancer

Abstract: Greater extent of lymphadenectomy was associated with increased survival for all patients with esophageal cancer except at the extremes (TisN0M0 and >or=7 regional lymph nodes positive for cancer) and well-differentiated pN0M0 cancer. Maximum 5-year survival is modulated by T classification: resecting 10 nodes for pT1, 20 for pT2, and >or=30 for pT3/T4 is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
255
5
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(281 citation statements)
references
References 18 publications
9
255
5
12
Order By: Relevance
“…A study with 2,303 patients from 9 international centers showed that the number of removed lymph nodes was an independent predictor of survival, and to maximize this benefit a minimum of 23 lymph nodes should be removed (55). Another study with 4,627 patients from leading international esophageal cancer centers showed the same results: improved survival rates following more extensive lymphadenectomy (17).…”
Section: Relation Of Lymphadenectomy and Survivalsupporting
confidence: 59%
See 2 more Smart Citations
“…A study with 2,303 patients from 9 international centers showed that the number of removed lymph nodes was an independent predictor of survival, and to maximize this benefit a minimum of 23 lymph nodes should be removed (55). Another study with 4,627 patients from leading international esophageal cancer centers showed the same results: improved survival rates following more extensive lymphadenectomy (17).…”
Section: Relation Of Lymphadenectomy and Survivalsupporting
confidence: 59%
“…There are authors who claim that the extent of lymphadenectomy should be associated with the stage of the tumor. Rizk et al recommended for pT1 to resect 10 lymph nodes, for pT2 20 lymph nodes and for pT3-4 at least 30 lymph nodes (17).…”
Section: Number Of Lymph Nodes To Be Resectedmentioning
confidence: 99%
See 1 more Smart Citation
“…Stilidi and Lerut (Stilidi et al, 2003;Lerut et al, 2004) demonstrated that an extended two-field or three-field lymphadenectomy could provide a higher rate of radical resection and improve the survival of esophageal SCC. Furthermore, based on the Worldwide Esophageal Cancer Collaboration data (Rizk et al, 2010), it was found that more extensive lymphadenectomy was associated with an improved survival in patients with esophageal cancer. Therefore, radical esophagectomy with extended lymph node dissection should be recommended to improve the prognosis of BSCCE.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports improved survival after esophagectomy with increased extent of lymphadenectomy (11). The robotic platform may allow for greater facility in lymphadenectomy to surgeons adopting minimally invasive approaches to esophagectomy, as nicely illustrated by the current cased study.…”
Section: Meticulous Attention To Clear Identification Of Vital Anatomymentioning
confidence: 86%